„NAUCZYCIEL NAJWIĘKSZĄ WARTOŚCIĄ NASZEGO NARODU” – RETORYKA, PRAKTYKA I SKUTKI „REFORMY” KSZTAŁCENIA NAUCZYCIELI W ANGLII I WALII - Potulicka, Eugenia (Rocznik Pedagogiczny, 2018)
Initial teacher training in England and Wales is radically reformed since the 2010 year. Many new ways of training were introduced, namely: School-Centered Initial Teacher Training, School Direct, apprenticeship, Teach First, Troops to Teachers and others. The role of universities in teacher train- ing is severe diminished with many implications for the quality of teachers and teaching as well as for the identity of academic teachers, their role and the lack of stability. Of course those changes have a lot of implications for universities, especially for their Schools of Education. Some of them disappeared.